Suono magico del violino come rito fondatore in Stabat Mater di Tiziano Scarpa - Puto, Małgorzata (Romanica Silesiana)
Tiziano Scarpa’s novel puts a great emphasis on the ritualistic expression in human life, which tends to be a meaningful and conscious way to expressing identity and personality. Music is a powerful means of expression for Cecilia, a young woman who considers herself as a weak creature. Deprived of any knowledge about her parents, she cannot find the way to fulfill social expectations and she is very vulnerable. Her talent to play the violin is linked to the concept of God, but then gives her the power to struggle against the world and all odds. In the music she plays, Cecilia can finally find her identity, and realizes that she is unique because of her music. Key words: rite, expression, music, identity